Nuclear Magnetic Resonance. Second Edition. By Peter Hore. Oxford University Press, 2015. Pp. 120. Price GBP 14.99. ISBN 9780198703419. Issue 4 (30th June 2017) - Bouguet-Bonnet, Sabine
Abstract : Book review Abstract : Book review